Research status of channel estimation and signal detection techniques for orthogonal time frequency space modulation - WANG Yongchuan; ZHOU Ping; HUANG Ju (Tongxin xuebao)
Orthogonal time frequency space (OTFS) modulation is a multiplexing technique designed in the two-dimensional (2D) delay-Doppler domain suited for high Doppler fading channels. OTFS converts a doubly-selective channel into an almost non-fading channel in the delay-Doppler domain through a series of 2D transformations. OTFS has the potential of capturing time-frequency full diversity. In order to obtain the time-frequency full diversity gain, a receiver with advanced channel estimation and signal detection algorithm is needed. The basic principle and system model of OTFS was firstly introduced, then the existing channel estimation and signal detection algorithms were reviewed, finally the future challenges and solutions for channel estimation and signal detection were discussed.